Nutrition adequacy level and elementary school students’ learning achievement / Kasmita Asmar Yulastri and Feri Ferdian - Asmar, Yulastri; Ferdian, Feri (Universiti Teknologi MARA Cawangan Selangor and UiTM Press, 2018)
This study investigates the relationship between nutrition adequacy level and the elementary school students learning achievement. Using descriptive research design through a quantitative method, this research surveyed fifty-four student parents of class IV, V and VI of Elementary School or Sekolah Dasar Pembangunan Laboratorium, Universitas Negeri Padang, Indonesia. Through the descriptive and inferential statistic, some useful insights pertaining to the issue investigated is significantly obtained. The nutritional adequacy and sufficiency of students still in the moderate level and the learning achievement still in the low level or the achievement content in the learning is still does not achieve the expected level. These persismitic indicators from the practical aspect convey varying consequences and implications especially to the student parents and the school authority.